Contribution of Arm Muscle Explosive Power and Eye-Hand Coordination to Servicing Accuracy at SMPN 21 Pekanbaru Volleyball Club: Kontribusi Daya Ledak Otot Lengan Dan Koordinasi Mata -Tangan Terhadap Ketepatan Servis Atas Klub Bolavoli SMPN 21 Pekanbaru - Fadhil, M; Alficandra, Alficandra (Badnur Medisa Group, 2024)
The aim of this research is to see the contribution of explosive power of the arm muscles, hand eye coordination to the accuracy of serves at the Junior High School 21 volleyball club Pekanbaru. The type of research used in this research is correlation research. The population in this study were all athletes from the Junior High School 21 volleyball club Pekanbaru, while the sampling technique in this study used total sampling, so the sample in this study was 17 people. The tests used in this research used the arm muscle explosive power test (two-hand medicine ball put), tennis ball throw and catch, and volleyball serve test. From the results of tests carried out on athletes from the Junior High School 21 volleyball club Pekanbaru, the results obtained were that there was a contribution between arm muscle explosive power to volleyball serves of 6.45%, there was a contribution between hand eye coordination to volleyball serves of 23.83% and There is a contribution of arm muscle explosive power and hand eye coordination to volleyball serves of 88.10%.